Rancang Bangun Aplikasi Pengelolaan Akun Zoom Meeting Di PT PLN Energi Primer Indonesia Berbasis Web - Rizal Mutakin; Munawar, Munawar (GLOBAL SCIENTS PUBLISHER, 2025)
Online meeting activities have become mandatory since the Covid-19 pandemic. PT PLN Energi Primer Indonesia has utilized the zoom cloud meeting application to use remote meetings for internal and external use. However, in practice, the process of ordering and creating meeting schedules is still done manually and has not been integrated so that this is felt to be less than optimal and can lead to errors caused by someone (human error) which results in clashes in the schedule for using the zoom meeting account. The purpose of this research is to design a web-based zoom meeting management application at PT PLN EPI. The system development method is Rapid Application Development (RAD). The system design uses the programming language PHP and MySQL as the database. System testing is done using black box testing. The results of this study are the successful creation of a web-based zoom meeting account management system at PT PLN EPI which is able to improve the quality of zoom meeting account management so that management related to zoom meeting scheduling can be carried out automatically because it is already integrated by the system, which can avoid clashes in the use of zoom accounts .